2018
DOI: 10.1007/s12663-018-1122-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of Quality of Life in Patients with Soft Tissue Reconstruction Following Mandibulectomy

Abstract: Purpose To study the effect of mandibulectomy with soft tissue reconstruction on quality of life (QOL) and functions of speech and swallowing. Methodology Quality of life of 66 patients was evaluated by using EORTC QLQ-C30 and EORTC-HN35 questionnaires. Speech was evaluated objectively by Dr. Speech software version 4 and subjectively by a single speech therapist along with swallowing. Patients were evaluated preoperatively and 6 months after treatment. Results Out of 66 patients, 57 followed up postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…They found improvements in the patients’ physical and cognitive roles and social and emotional functions but increases in fatigue, nausea, vomiting, dyspnea, appetite loss, swallowing, speech, and xerostomia due to chemoradiation. Pain and nutrition improved as patients were disease-free and tube-fed, and there was a marginal improvement in the overall QoL 20. We hope to embark on a similar comparative study with a larger sample size (for each group of patients) in the future.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They found improvements in the patients’ physical and cognitive roles and social and emotional functions but increases in fatigue, nausea, vomiting, dyspnea, appetite loss, swallowing, speech, and xerostomia due to chemoradiation. Pain and nutrition improved as patients were disease-free and tube-fed, and there was a marginal improvement in the overall QoL 20. We hope to embark on a similar comparative study with a larger sample size (for each group of patients) in the future.…”
Section: Discussionmentioning
confidence: 93%
“…Pain and nutrition improved as patients were disease-free and tube-fed, and there was a marginal improvement in the overall QoL. 20 We hope to embark on a similar comparative study with a larger sample size (for each group of patients) in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Our data showed that segmental resections not only required significantly longer operation time but also led to a longer hospital stay ( p < 0.001 and 0.025, respectively). Furthermore, segmental resections also bear a significant loss in the quality of life of patients (Dholam et al 2019 ; Rogers et al 2004 ). Still, with regard to recurrences, few compromises in the case of mandibular infiltrations are possible (Gou et al 2018; Li et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%